Clinicopathological significance and potential drug target of T-cadherin in NSCLC - Wang Z; Wang B; Guo H; Shi G; Hong X (Dove Medical Press, 2014)
Zhidong Wang,1 Bin Wang,1 Huanchen Guo,2 Guoyu Shi,2 Xiuqin Hong3 1Oncology Department, Eighth Hospital of Changsha, Changsha, People’s Republic of China; 2Department of Respiratory Medicine, Shouguang Hospital of Traditional Chinese Medicine, Shouguang, People’s Republic of China; 3Institute of Gerontology, Hunan Geriatric Hospital, Changsha, People’s Republic of China Background: Previous studies demonstrate that T-cadherin is a candidate tumor suppressor in several types of human tumors, including non-small cell lung cancer (NSCLC). Lack of protein expression of T-cadherin by hypermethylation has been found to play an important role in lung alveolar differentiation regulation and epithelial tumorigenesis. However, the correlation between T-cadherin hypermethylation and clinicopathological characteristics of NSCLC remains unclear. Here we conducted a systematic review and meta-analysis to quantitatively evaluate the effects of T-cadherin hypermethylation on the incidence of NSCLC and clinicopathological characteristics.Methods: A detailed literature search was carried out for related research publications. Analyses of pooled data were performed. Odds ratio (OR) and hazard ratio (HR) were calculated and summarized, respectively.Results: Final analysis of 1,172 NSCLC patients from 15 eligible studies was performed. T-cadherin hypermethylation was observed to be significantly higher in NSCLC than in normal lung tissue, based on the pooled OR from nine studies including 532 NSCLC and 372 normal lung tissue samples (OR=8.19, 95% confidence interval [CI]=5.41–12.39, P<0.00001). T-cadherin hypermethylation may also be associated with pathological types. The pooled OR was obtained from four studies including 111patients with squamous cell carcinoma and 106 with adenocarcinoma (OR=0.35, 95% CI=0.19–0.66, P=0.001), which indicated that T-cadherin hypermethylation plays a more important role in the pathogenesis of adenocarcinoma. We did not find that T-cadherin hypermethylation was correlated with the sex or smoking status, clinical stages, or epidermal growth factor receptor (EGFR) mutation status. However, T-cadherin hypermethylation was found to be significantly higher in poorly differentiated NSCLC than in moderately and highly differentiated NSCLC, and NSCLC patients with T-cadherin hypermethylation had a lower survival rate than those without T-cadherin hypermethylation.Conclusion: The results of this meta-analysis suggest that T-cadherin hypermethylation is associated with an increased risk and worse survival in NSCLC. T-cadherin hypermethylation, which induces the inactivation of T-cadherin gene, plays an important role in the carcinogenesis, cancer progression, as well as clinical outcome. Keywords: methylation, lung cancer, meta-analysis, EGFR, odds ratio, hazard ratio